Circular Reporting, Strategy and Performance in Agri-Food Companies: A Natural Resource-Based Theoretical Approach; [Reporting, Estrategia y Desempeño de Economía Circular en Empresas Agroalimentarias: Análisis Desde el Enfoque Teórico Basado en Recursos Naturales] - Jara-Sarrua, L (Universidad de Murcia, 2023)
Awareness about the circular economy as a sustainability paradigm is growing globally, being the agri-food sector one of the most significant industries moving towards circular operations. The natural resourcebased view theory can provide a basis to analyze organizational resources and capabilities allowing a clear definition of circular economy strategies and performance. How accounting and reporting can leverage these concepts, is being debated currently at the academic level. In this context, this study examines to what extent Argentinian agri-food organizations use circular reporting to translate circular economy strategy into better performance. Survey data were collected from 238 agri-food Argentinian organizations and analyzed using partial least squares structural equation modeling (PLS-SEM). General results show that a natural resource-based circular economy strategy positively affects performance and circular reporting has a significant indirect effect on environmental and economic performance, through the improvement of natural resource-based circular economy strategies. © 2023 ASEPUC.